Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/14651858.cd006594.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Reminder systems to improve patient adherence to tuberculosis clinic appointments for diagnosis and treatment

Abstract: BackgroundPeople with active tuberculosis (TB) require six months of treatment. Some people find it difficult to complete treatment, and there are several approaches to help ensure completion. One such system relies on reminders, where the health system prompts patients to attend for appointments on time, or re-engages people who have missed or defaulted on a scheduled appointment.ObjectivesTo assess the effects of reminder systems on improving attendance at TB diagnosis, prophylaxis, and treatment clinic appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
1
65
0
1
Order By: Relevance
“…12 These ED-specific findings are consistent with previous studies demonstrating improved follow-up adherence in other health care settings when text messaging was used. 6 This study is not without limitations. The main limitation of this study is that it is a nested cohort analysis within a small RCT conducted at a single academic centre.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…12 These ED-specific findings are consistent with previous studies demonstrating improved follow-up adherence in other health care settings when text messaging was used. 6 This study is not without limitations. The main limitation of this study is that it is a nested cohort analysis within a small RCT conducted at a single academic centre.…”
Section: Discussionmentioning
confidence: 89%
“…3 This method of communication has been effective in the health care setting to provide appointment reminders, facilitate self-management of chronic illnesses, and encourage medication adherence. [4][5][6] Several reviews of the literature have illustrated wide application and potential for mobile phones to increase access to health care; enhance the efficiency of service delivery; improve diagnosis, treatment, and rehabilitation; and support public health. [4][5][6] Despite the widespread application of text messaging to facilitate health care delivery, there is a paucity in the literature supporting the use of text messaging to facilitate clinical research, specifically to assist in research participant follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential intervention would be to combine SMS reminders with off-site support as the Lester et al (2010) trial did for HIV patients in Kenya. SMS reminders could also be used to remind patients of clinic appointments, as various forms of reminders (telephone calls, home visits, letters) for clinic appointments have been found to be beneficial in studies with TB patients (Liu et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The proposed solution of 'directly observed therapy' (DOT), a practice that involves healthcare practitioners observing patients taking their treatment, is not well supported by systematic review evidence regarding distinct approaches to implementation of directly observed therapy [9], including incentives and enablers [10], or reminders [11]. Whilst these reviews, drawing on randomised controlled trials, provided some useful inputs to specific technical recommendations being made by the World Health Organization at the time, in broader policy terms they offer disappointing findings to national policy makers frustrated by the "real world" where: conflicts disrupting health systems; practitioners favouring patients they considered most deprived and therefore most deserving; and patients finding the timing of the treatment and incentive (a midday meal) inconvenient [10].…”
Section: Box 2 the Mismatch Between The Worlds Of Research And Implemmentioning
confidence: 99%